2016
DOI: 10.5222/head.2016.253
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the knowledge levels of healthcare staff in the diagnosis and prevention of development of phlebitis and thrombophlebitis associated with intravenous infusion therapy

Abstract: ÖZAmaç: Bu çalışmada; intravenöz infüzyon tedavisine bağlı ebit ve trombo ebit gelişimini önleme ve tanılamada, sağlık çalışanlarının bilgi düzeylerinin belirlenmesi amaçlanmıştır. Gereç ve Yöntem:Tanımlayıcı nitelikte olan çalışmanın evreni ve ör-neklemini, 02.09.2013 -01.01.2014 tarihleri arasında İstanbul'da özel bir hastane ve üç eğitim araştırma hastanesinin yoğun bakım üniteleri ile yatan hasta katlarında intravenöz tedavi uygulayan ve araştırmaya katılmayı kabul eden gönüllü 100 hemşire, 12 ebe, 4 acil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Studies have shown that the knowledge of nurses regarding the prevention of PIT differs in relation to their personal and professional characteristics. 1,[13][14][15] Accurate documentation provides guidance which outlines nurses' professional accountability in recordkeeping for all nursing routine practices. 14 From examining the practices of the participant in the current study, it was seen that all of the nurses documented PIT complications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that the knowledge of nurses regarding the prevention of PIT differs in relation to their personal and professional characteristics. 1,[13][14][15] Accurate documentation provides guidance which outlines nurses' professional accountability in recordkeeping for all nursing routine practices. 14 From examining the practices of the participant in the current study, it was seen that all of the nurses documented PIT complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the knowledge of nurses regarding the prevention of PIT differs in relation to their personal and professional characteristics. 1,13–15…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations